2001
DOI: 10.1046/j.1365-2141.2001.02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe and long‐lasting disruption of T‐cell receptor diversity in human myeloma after high‐dose chemotherapy and autologous peripheral blood progenitor cell infusion

Abstract: Summary. Vaccine-based strategies are currently under investigation as a means of inducing tumour-specific immune responses and improving the clinical outcome of multiple myeloma (MM) patients in remission after highdose chemotherapy and peripheral blood progenitor cell (PBPC) infusion. The immune competence of these patients was investigated by determining the overall diversity of the T-cell receptor (TCR) repertoire in the peripheral blood (PB) and bone marrow (BM). The average time after transplantation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…26,27 Therefore, assuming that T cells with a naive phenotype contain the largest fraction of the TcR repertoire, 28 it could be speculated that the starting pool of mature T cells may provide a substantial lymphopoietic support to the severe disruption of TcR diversity in the early phase after HD-ChT. 29 The question remains as to whether high numbers of T cells in the grafts may confer not only more rapid T-cell reconstitution, but also better immune competence and perhaps overall prognosis. 30 In fact, following HD-ChT, patients are more susceptible to opportunistic infections and to reactivation of persistent virus after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Therefore, assuming that T cells with a naive phenotype contain the largest fraction of the TcR repertoire, 28 it could be speculated that the starting pool of mature T cells may provide a substantial lymphopoietic support to the severe disruption of TcR diversity in the early phase after HD-ChT. 29 The question remains as to whether high numbers of T cells in the grafts may confer not only more rapid T-cell reconstitution, but also better immune competence and perhaps overall prognosis. 30 In fact, following HD-ChT, patients are more susceptible to opportunistic infections and to reactivation of persistent virus after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…35 Recovery from transplantation and hematological remission are followed by restoration of the polyclonal TCR repertoire. 36,37 5. False-positive results: False-positive results are rare by Southern blot analysis and can generally be prevented by checking for underdigestion and by excluding polymorphic restriction sites.…”
Section: Limitations and Pitfalls Of Molecular Clonality Studiesmentioning
confidence: 99%
“…19 We distinguished four CDR3 size distribution patterns: (1) normal, with a Gaussian distribution of BV-BC CDR3 fragments; (2) reactive, with one or more peaks above the normal Gaussian background; (3) deteriorated, in which the Gaussian distribution was replaced by two or more predominant peaks; and (4) single peak, with a prominent single peak. The TCRBV repertoire was evaluated in eight patients before vaccination, during vaccination, and 6 and 12 months after the last immunization.…”
Section: Immunological Monitoringmentioning
confidence: 99%
“…Determination of the clonality and reciprocal usage of BV gene segments has shown that the TCR repertoire is severely disrupted in MM patients after high-dose chemotherapy and PBPC infusion. 19 On average, one-third consists of T cells expressing oligoclonal or abnormal TCRBV transcripts. 19 A progressive recovery of TCR diversity was observed following the start of vaccination, as shown by the increase of polyclonal and the decrease of abnormal TCRBV transcripts.…”
Section: Idiotype Vaccination In Human Myelomamentioning
confidence: 99%